A Comparison of GFR Estimation Formulae in Pediatric Oncology - Rechenauer, Tobias; Zierk, Jakob; Gräfe, Daniel; Rascher, Wolfgang; Rauh, Manfred; Metzler, Markus (Klinische Pädiatrie, 2018)
Background Application of potentially nephrotoxic chemotherapy requires continuous monitoring of renal function for toxicity and dosing. Novel pediatric glomerular filtration rate (GFR) estimating equations including cystatin C have been proposed to enhance the reliability of GFR calculation.Materials and methods We examined a pediatric oncologic data set with a total of 363 GFR measurements. An analysis of distribution characteristics and comparison of medians was performed to compare creatinine and cystatin C-based GFR estimating formulae. Furthermore, we investigated the clinical impact of different equations in regard to therapeutic consequences.Results Significant differences in estimated GFR values were calculated depending on the applied formula (range of median GFR from 94.8 to 180.9 mL/min per 1.73 m2) which may result in different therapeutic consequences for the use of potentially nephrotoxic chemotherapeutic agents. Significant correlation for all examined formulae was identified, however there were large fluctuations among the correlation coefficients ranging from 0.254 to 1.0.Conclusion This study compares proposed pediatric GFR estimating equations in a clinical setting. It underlines the current limitations and difficulties of GFR estimation including potential dosing errors. Cystitis C-based equations can be used as alternatives to creatinine-based estimations when the appropriate laboratory method has been applied. A comparative calculator for pediatric GFR estimating equations along with background information is provided at http://gfr.pedz.de and may support clinical decision-making.
Keywords: renal function; cystatin C; GFR; glomerular filtration rate estimating equation; creatinine clearance; nephrotoxic substances